Gender Differentials Among Teachers’ Classroom Management Strategies In Pakistani Context (Journal of Education and Educational Development, 2020)
The main purpose of this study was to get an insight about teachers’ classroom management strategies and explore the gender differences among teachers’ classroomstrategies. The present descriptive study was quantitative in nature andmethod was used. All the teachers, teaching in different Islamabad Model Schools for Boys and Girls, Islamabad (Urban Sector) constituted the population of the. Data were collected from a sample of 126 secondary school teachers, teaching in 10 different Islamabad Model Schools for Boys and Girls, Islamabad, Pakistan. Data were collected via Classroom Management Inventory (CMI), developed by the researcher, keeping in view the Pakistani context. As a result of pilot study, reliability test of the questionnaire reflected 0.947 value of Cronbach’s Alpha, which showed the high reliability of the instrument. From the findings of the study, it was concluded that teachers’ gender affects their classroom management. Female teachers exhibited more classroom management skills on four out of six dimensions of classroom management than the male teachers. Classroom management being a challenging and complex task, demand knowledge and skills on the part of teachers. It is recommended that teacher trainings should contribute to such endeavour, keeping in view the gender differentials.